PROMOTING RESPONSIBLE ENVIRONMENTAL BEHAVIOR OF STUDENTS IN BIOLOGY DEPARTMENT BY THE IMPLEMENTATION OF ENVIRONMENTAL EDUCATION - Setiyaningsih, Dwi; Poedjiastoeti, Sri; Raharjo, Raharjo; Atweh, Bill (JPPS (Jurnal Penelitian Pendidikan Sains), 2012)
Eco Campus is a national environmental management system and award scheme for the higher education sector for addressing key issues of environment. One of the education institutions at university level that was planned to implement an eco- campus is the State University of Surabaya (UNESA) especially at the Faculty of Mathematics and Science (FMIPA). However, to create such goal, it was important to begin with how to make the students have responsible environmental behavior (REB). Related to such problem, the pre experimental research has been conducted to promote three of responsible environmental behavior of students in Biology department of international class 2012, comprised of; eco-management action, persuasion, and economic/consumer action using the implementation of environmental education program. As a lifelong study, the environmental education was aimed to show that interdependency between humanity and the environment was needed to improve the human environment sustainability for the present and the future generations. This study was conducted using variety of data sources; observation, interview, questionnaire and test. Based on the data analyses descriptively and the discussion result, it was known that the ability of the lecturer to manage the learning activities for each category was good. Then, the implementation of environmental education program can promote three categories of responsible environmental behaviors of students. Moreover, the environmental education implemented in the current research has positive impact on students? cognitive learning outcomes of environmental knowledge subject, especially the strategies for sustainable development topic, based on the UNESA grade standard.Eko-kampus adalah sebuah sistem manajemen lingkungan nasional dan skema penghargaan untuk sektor pendidikan tinggi untuk mengatasi permasalahan utama lingkungan. Salah satu lembaga pendidikan di tingkat universitas yang telah mencanangkan eko-kampus adalah Universitas Negeri Surabaya (UNESA) khususnya di Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA). Namun demikian, untuk mewujudkan tujuan tersebut, hal terpenting yang harus dipertimbangkan adalah bagaimana cara membentuk sikap mahasiswa memiliki perilaku yang bertanggung jawab terhadap lingkungan (REB).Terkait dengan permasalahan tersebut, penelitian pra-eksperimen telah dilakukan untuk mendorong terwujudnya tiga aspek perilaku yang bertanggung jawab terhadap lingkungan pada mahasiswa jurusan Biologi kelas internasional 2012, meliputi, tindakan eko-manajemen, persuasi, dan tindakan konsumen/ekonomi, melalui penerapan program pendidikan lingkungan. Sebagai pendidikan seumur hidup, pendidikan lingkungan bertujuan untuk menunjukkan bahwa saling ketergantungan antara manus ia dan lingkungan diperlukan untuk meningkatkan kelestarian lingkungan hidup manusia untuk saat ini dan generasi yang akan datang. Penelitian ini dilakukan dengan menggunakan berbagai teknik pengumpulan data meliputi, observasi, wawancara, angket dan tes. Berdasarkan analisis data secara deskriptif dan hasil pembahasan, diketahui bahwa kemampuan pengajar dalam mengelola aktivitas pembelajaran untuk setiap langkah pengajaran adalah baik. Kemudian, pelaksanaan program pendidikan lingkungan dapat mendorong tiga aspek perilaku yang bertanggung jawab terhadap lingkungan pada mahasiswa. Selain itu, pendidikan lingkungan yang telah diterapkan dalam penelitian ini memiliki dampak positif terhadap hasil belajar kognitif mahasiswa pada mata kuliah pengetahuan lingkungan, terutama pada materi strategi untuk pembangunan berkelanjutan, berdasarkan pada standar penilaian UNESA.